Manoeuvres in manual person-to-parts order picking systems: Is there a significant influence on travel time and metabolic rates?. Issue 1 (July 2017) - Elbert, Ralf; Philipp Müller, Jan
Abstract: In current planning models for travel time calculation in manual person-to-parts order picking systems it is assumed that the order picker travels at constant velocity through the warehouse. Curves and turn manoeuvres that are necessary for changing the aisles are neglected in operating strategies so far. For order pickers that use a cart for transporting the items a more realistic approach would be to consider additional time for those manoeuvres due to a reduced gait velocity as well as additional physical exposure due to higher pushing/pulling forces. The paper at hand investigates if those influences should be further deliberated in travel time calculation and in ergonomic evaluation by the means of a simulation study. First results show that especially for small warehouse dimensions and random storage assignment policies warehouse operators could prefer heuristic routing policies (combined/composite/traversal) instead of the optimal (minimal travel distance) policy when taking curves/turn manoeuvers into account.